Speech and computer : 20th International Conference, SPECOM 2018, Leipzig, Germany, September 18-22, 2018, Proceedings /: 20th International Conference, SPECOM 2018, Leipzig, Germany, September 18-22, 2018, Proceedings. (2018) - Unknown
No abstract available